Development and validation of a headspace gas chromatographic method for the determination of residual solvents in arterolane (RBx11160) maleate bulk drug - Abhishek Gupta; Yogendra Singh; Kona S Srinivas; Garima Jain; V B Sreekumar; Vinod Prasad Semwal (Wolters Kluwer Medknow Publications, 2010)
Objective : Arterolane maleate is an antimalarial drug currently under Phase III clinical evaluation, and presents a simple, economical and scalable synthesis, and does not suffer from safety problems. Arterolane maleate is more active than artemisinin; and is cheap to produce. It has a longer lifetime in the plasma, so it stays active longer in the body. To provide quality control over the manufacture of any API, it is essential to develop highly selective analytical methods. In the current article we are reporting the development and validation of a rapid and specific Head space gas chromatographic (HSGC) method for the determination of organic volatile impurities (residual solvents) in Arterolane Maleate bulk drug. Materials and Methods : The method development and its validation were performed on Perkin Elmer's gas chromatographic system equipped with Flame Ionization detector and head space analyzer. The method involved a thermal gradient elution of ten residual solvents present in arterolane maleate salt in RTx-624, 30 m Χ 0.32 mm, 1.8 μ column using nitrogen gas as a carrier. The flow rate was 0.5 ml/min and flame ionization detector (FID) was used. Results : During method validation, parameters such as precision, linearity, accuracy, limit of quantification and detection and specificity were evaluated, which remained within acceptable limits. Conclusions : The method has been successfully applied for the quantification of the amount of residual solvents present in arterolane maleate bulk drug.The method presents a simple and reliable solution for the routine quantitative analysis of residual solvents in Arterolane maleate bulk drug.